Adopting e-hailing application among Malaysian millennials. - Mohamed Razi, Mohamed Jalaldeen; Mohd Tamrin, Mohd Izzuddin; Mohd. Nor, Rizal (IEEE, 2020)
e-hailing apps dominate the public taxi transport sector all over the globe. Different researchers study this disruptive business model from a different perspective. The current researchers look at this phenomenon from the technology acceptance perspective. Technology Acceptance Model (TAM) make the base for the study. The variables Performance Expectancy (PE) and the Effort Expectancy (EE) and another two variables Trust, and Enjoyment are also considered in this study. Data were collected from 352 university students who are millennials. Out of the four hypotheses proposed, Effort Expectancy (H2), Trust (H3), and Enjoyment (H4) positively influence Intention. The hypothesis related to PE (H1) was not supported. Implications are discussed.